2021
DOI: 10.1210/endocr/bqab166
|View full text |Cite
|
Sign up to set email alerts
|

LH Induces De Novo Cholesterol Biosynthesis via SREBP Activation in Granulosa Cells During Ovulation in Female Mice

Abstract: In the liver, the sterol response element binding protein (SREBP) and the SREBP cleavage-activated protein (SCAP) complex upregulates cholesterol biosynthesis by gene induction of de novo cholesterol synthetic enzymes (Hmgcr, Cyp51, and Dhcr7). Insulin induced gene 1 (INSIG1) negatively regulates cholesterol biosynthesis by the inhibition of de novo cholesterol biosynthetic gene expression. In the ovary, cholesterol is de novo synthesized; however, the roles of SREBP and its regulators (SCAP and INSIG1) are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…While its role during gonad development is not clearly established, several potassium channels are known to participate in the regulation of progesterone secretion (Kim et al 2020 ). Dhcr7 encodes an enzyme involved in the cholesterol biosynthesis (Nakanishi et al 2021 ). It has been identified as a biomarker of exposure to KTZ and DES in human adult ovarian cortex cultures (Li T et al Unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…While its role during gonad development is not clearly established, several potassium channels are known to participate in the regulation of progesterone secretion (Kim et al 2020 ). Dhcr7 encodes an enzyme involved in the cholesterol biosynthesis (Nakanishi et al 2021 ). It has been identified as a biomarker of exposure to KTZ and DES in human adult ovarian cortex cultures (Li T et al Unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…shown that SREBP-1c and SREBP cleavage-activating protein (SCAP) complex induce cholesterol biosynthesis in the liver by upregulating the gene expressions of cholesterol synthases (Hmgcr, Cyp51 and Dhcr7) (32). Besides, SREBP-1c regulates the transcription of downstream lipid synthesis-related genes Acaca and Fasn (33).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription was performed as recently described. 16 Briefly, isolated total RNA (5 ng/μL) was reverse-transcribed using 500 ng of poly-dT (Promega) and 0.25 U of avian myeloblastosis virus reverse transcriptase (Promega) for 75 min at 42°C and for 5 min at 95°C. Real-time PCR analysis was performed as we described recently.…”
Section: Real Time Rt-pcr Analysismentioning
confidence: 99%
“…Real-time PCR analysis was performed as we described recently. 16 Briefly, cDNA and primers were added to the KAPA SYBER FAST Universal qPCR kit (Kapa Biosystems) to give a total reaction volume of 15 μL. PCR was then performed using the MiniOpticon Real-Time PCR Detection Systems (Bio-Rad).…”
Section: Real Time Rt-pcr Analysismentioning
confidence: 99%